2019
DOI: 10.1021/acs.analchem.9b01647
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Phenotypic Profiling of CTCs in Whole Blood Using an Integrated Microfluidic Device

Abstract: Single-cell phenotypic profiling of circulating tumor cells (CTCs) in the blood of cancer patients can reveal vital tumor biology information. Even though various approaches have been provided to enrich and detect CTCs, it remains challenging for consecutive CTC sorting, enumeration, and single-cell characterizations. Here, we report an integrated microfluidic device (IMD) for single-cell phenotypic profiling of CTCs that enables automated CTCs sorting from whole blood following continuous single-cell phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…For example, the biological affinity method depends on exogenous markers, which often affect the cell activity of CTCs, while the physical screening method has low separation accuracy and is easy to produce false-positive results. Therefore, the researchers tried to combine the two methods ( Pei et al 2019 ; Lee, et al, 2017 ), effectively remove leukocytes using a label-free method, and then separate CTCs with high efficiency and purity using an affinity-based method. Song et al (2019) designed a deterministic lateral displacement (DLD) pattern microfluidic chip modified with multivalent aptamer functionalized nanospheres (AuNP-syl3c) based on the principle of deterministic lateral displacement ( Figure 5A ).…”
Section: Microfluidic Technologies For Ctcs Separationmentioning
confidence: 99%
“…For example, the biological affinity method depends on exogenous markers, which often affect the cell activity of CTCs, while the physical screening method has low separation accuracy and is easy to produce false-positive results. Therefore, the researchers tried to combine the two methods ( Pei et al 2019 ; Lee, et al, 2017 ), effectively remove leukocytes using a label-free method, and then separate CTCs with high efficiency and purity using an affinity-based method. Song et al (2019) designed a deterministic lateral displacement (DLD) pattern microfluidic chip modified with multivalent aptamer functionalized nanospheres (AuNP-syl3c) based on the principle of deterministic lateral displacement ( Figure 5A ).…”
Section: Microfluidic Technologies For Ctcs Separationmentioning
confidence: 99%
“…This revealed the differences in metabonomic characteristics among CTCs from different tumor populations. Pei et al [ 120 ] reported an integrated microfluidic device for the phenotypic analysis of a single CTC. This device can allow the automatic isolation of CTCs from whole blood after sequential single-cell phenotyping with high-purity (92% ± 3%) cell sorting and high-throughput processing capacity (5 mL/3 h).…”
Section: Clinical Applications Of Ctcsmentioning
confidence: 99%
“…By integrating two-color fluorescence signal coding on a microfluid chip with fabricated spiral and pillar array microstructures, Pei et al simultaneously monitored EpCAM and E-cadherin expression on single CTCs (Figure 7a). [92] On the basis of microfluidic movement within the constructed microstructures, CTCs were firstly isolated from whole blood prior to membrane protein biomarker profiling with consecutive fluorescence coding and laser-induced detection. The CTC profiling of 90 colorectal cancer patients revealed a close relationship of CTC profile with tumor progression.…”
Section: Fluorescence Coding Of Multiple Biomarkersmentioning
confidence: 99%
“…Reproduced with permission. [92] Copyright 2019, American Chemical Society. b) A microfluidic platform for CA-125, EpCAM, and CD24 protein profiling on ovarian cancer-derived exosomes.…”
Section: Fluorescence Coding Of Multiple Biomarkersmentioning
confidence: 99%